Genocias ir rezistencija Nr. 25(1) - Boćkowski, Daniel; Bubnys, Artūras; Pocius, Mindaugas; Burinskaitė, Kristina; Banionis, Juozas; Grybkauskas, Saulius; Kaminskaitė, Lina (Genocidas ir rezistencija, 2009)
Pilnas leidinys